Multi-Gene Phylogeny of the Ciliate Genus Trachelostyla (Ciliophora, Hypotrichia), With Integrative Description of Two Species, Trachelostyla multinucleata Spec. nov. and T. pediculiformis (Cohn, 1866) - Zhang, Tengyue; Shao, Chen; Zhang, Tengteng; Song, Weibo; Vd’ačný, Peter; Al-Farraj, Saleh A.; Wang, Yurui (Frontiers in Microbiology, 2022)
Many hypotrich genera, including Trachelostyla, are taxonomically challenging and in a need of integrative revision. Using morphological data, molecular phylogenetic analyses, and internal transcribed spacer 2 (ITS2) secondary structures, we attempt to cast more light on species relationships within the genus Trachelostyla. The present multifaceted approach reveals that (1) a large-sized species with numerous macronuclear nodules, isolated from sandy littoral sediments in southern China, is new to science and is endowed here with a name, T. multinucleata spec. nov.; (2) two other Chinese populations previously identified as T. pediculiformis represent undescribed species; and (3) multigene phylogeny is more robust than single-gene trees, recovering the monophyly of the genus Trachelostyla with high bootstrap frequency. Additionally, ITS2 secondary structures and the presence of compensatory base changes in helices A and B indicate the presence of four distinct taxa within the molecularly studied members of the genus Trachelostyla. Molecular data are more suitable for delimitation of Trachelostyla species than morphological characters as interspecific pairwise genetic distances of small subunit (18S) rDNA, ITS1-5.8S-ITS2, and large subunit (28S) rDNA sequences do not overlap, whereas ranges of multiple morphometric features might transcend species boundaries.